2017
DOI: 10.1590/s1806-37562017000000139
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the STOP-Bang questionnaire as a means of screening for obstructive sleep apnea in adults in Brazil

Abstract: Objective:To validate the Portuguese-language version of the STOP-Bang (acronym for Snoring, Tiredness, Observed apnea, high blood Pressure, Body mass index, Age, Neck circumference, and Gender) questionnaire, culturally adapted for use in Brazil, as a means of screening for obstructive sleep apnea (OSA) in adults. Methods:In this validation study, we enrolled patients ≥ 18 years of age, recruited between May of 2015 and November of 2016. All patients completed the STOP-Bang questionnaire and underwent overnig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
2
33
0
1
Order By: Relevance
“…The STOP-Bang instrument presented different versions developed in order to try to improve the diagnosis of OSAS and to discriminate the subgroups with mild, moderate and severe OSAS, in addition to adapting it to constitutional anatomical differences of patients from other countries 5,8,10,11,22.29 . There is another validated version for the Portuguese language spoken in Brazil, which incorporates different values of cervical circumference (greater than 43 cm for men and 41 cm for women), with final scores ranging from low and moderate to high risk of OSAS; this version had a slightly higher sensitivity (83.5%) for the Brazilian sample, but a much lower specificity (45.5%) than the version used for us 31,32 . Thus, our proposal of different cutoff points for OSAS in general, and for the mild, moderate and severe subtypes, could improve the performance of the instrument in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The STOP-Bang instrument presented different versions developed in order to try to improve the diagnosis of OSAS and to discriminate the subgroups with mild, moderate and severe OSAS, in addition to adapting it to constitutional anatomical differences of patients from other countries 5,8,10,11,22.29 . There is another validated version for the Portuguese language spoken in Brazil, which incorporates different values of cervical circumference (greater than 43 cm for men and 41 cm for women), with final scores ranging from low and moderate to high risk of OSAS; this version had a slightly higher sensitivity (83.5%) for the Brazilian sample, but a much lower specificity (45.5%) than the version used for us 31,32 . Thus, our proposal of different cutoff points for OSAS in general, and for the mild, moderate and severe subtypes, could improve the performance of the instrument in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were divided into three categories according to SD: short sleep (<6 hours/24 hours), intermediate sleep (6-8 hours/24 hours), and long sleep (>8 hours/24 hours). The risk of OSA, a potential confounder of the relationship between SD and GC, was determined by the Brazilian version of the STOP-BANG questionnaire [27] (score ≥ 3 used as a risk indicator). Excessive daytime somnolence (EDS) was evaluated by the Brazilian version of the Epworth Sleepiness Scale [28] (score > 10 identified EDS).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the STOP-Bang questionnaire showed the best performance in a population at risk for OSAS, similar to what was reported in a study conducted in Brazil. 9 In a systematic review and meta-analysis, a STOP-Bang cutoff score ≥ 3 had an AUC of 0.72 (with a sensitivity and specificity of 90% and 49%, respectively) for predicting an AHI ≥ 5 events/h. 10 For predicting an AHI ≥ 30 events/h, the authors found the sensitivity and specificity of that same cut-off score to be 96% and 25%, respectively.…”
Section: To the Editormentioning
confidence: 99%
“…In our validation cohort (private clinic group), contingency tables showed that those cut-off points still had the best sensitivity and specificity for Performance of instruments aimed at detecting obstructive sleep apnea syndrome among individuals in Chile In the present study, the STOP-Bang questionnaire showed the best performance in a population at risk for OSAS, similar to what was reported in a study conducted in Brazil. (9) In a systematic review and meta-analysis, a STOP-Bang cutoff score ≥ 3 had an AUC of 0.72 (with a sensitivity and specificity of 90% and 49%, respectively) for predicting an AHI ≥ 5 events/h. (10) For predicting an AHI ≥ 30 events/h, the authors found the sensitivity and specificity of that same cut-off score to be 96% and 25%, respectively.…”
mentioning
confidence: 99%